Caudal analgesia and cardiothoracic surgery: a look at postoperative pain scores in a pediatric population. Issue 11 (23rd August 2016) - Nguyen, Khoa N.; Byrd, Heather S.; Tan, Jonathan M.
Summary: Aim: Caudal epidural anesthesia has been shown to reduce stress response and shorten the time to extubation in children after cardiac surgery. Combined with general anesthesia, regional anesthesia has been proven to be safe and efficacious in the pediatric population. It is not known, however, whether the use of caudal anesthesia actually reduces postoperative pain scores and decreases postoperative opioid use. Methods: We retrospectively analyzed the charts of 199 children who underwent repair for atrial septal defect (ASD), ventricular septal defect (VSD), and Tetralogy of Fallot (TOF) at a major academic children's hospital between 2010 and 2013. Results: Eighty‐six patients underwent preoperative placement of caudal anesthesia (bupivacaine 0.25% 1 ml·kg −1 up to 20 ml + clonidine 2mcg·kg −1 + Duramorph 40 mcg·kg −1 up to 2.5 mg) and 113 patients did not have a caudal block. Postoperative cardiac intensive care pain scores were analyzed according to standard nurse‐recorded patient‐appropriate pain scales ranging from 0 to 10 (CRIES for neonates and FLACC for 2 months–7 years). There was no statistical difference between caudal and noncaudal groups with respect to postoperative pain scores or with postoperative opioid requirements. There was a statistical significance with regard to intraoperative opioid use as noncaudal patients invariably received more opioid during the procedure. Conclusion: Although regional anesthesia reduced intraoperative opioid usage, there was no difference in postoperative opioid usage or pain scores. Abstract :